Políticas ambientais no Timor Leste: perspectivas para o ensino de ciências - Guterres, Lara Maria Aquino (2013)
From the beginning of 2003 there was great discussion between government and national and local ONGs, on the environmental degradation and his consequences in the life of the current society and for the future generations of the East Timor. Standing up questions be left as destruction will recover the environment after so many years along the history of the Country. It approached to a resolution in the agreement that from the unity of environmental management and of natural resources looks to shorten the poverty of the environment. Taking some references as a base at world-wide level like the international convention of Kyoto, convention of Vienna and the protocol of Montreal, which board interesting questions in level of protection of the natural resources, like the discussion on climatic changes and greenhouse effect, study of the gases that destroys the ozone layer, so the government of East Timor raises a politics of the management of the environment, to control all the activities and the spaces of the community to preparation of plans of strategies that aim to protect the forests and consequently the biodiversity of existent one in each ecosystem, allowing so the food security, for part of the maintenance of the diversity of foods and so to be admitted the development of the economy and sustainable environment. Why the use of these resources in the present do not they compromise the future generations, be for the indisponibility of same in the nature or with more serious consequences like environmental disasters. With discovery of this politics and environmental management, in the DNMA and ONG, through the inquiry, search to answer the central question: what are the central questions what the place occupies in the discussion of the official texts of the East Timor? Having principal objective to analyst and to identify the question what, the central place of the discussions occupies in the official texts of the public environmental politics in East Timor; To know the environmental politics in the school and in the community. The worn-out methodology was based on the idea of Gil (1999) of descriptive inquiry exploratory, where hypotheses were prepared and from them questionnaire was prepared with 15 open questions and 07 specific questions, where the interviewed ones did an evaluation of the environmental situation connecting with the political, social and economical questions. One is known that still the inquiries made a list to the environment in the healthy East Timor incipient, what they have been advancing according to the Country has if developed, since due to the lack of equipments, and physical structure for realization of the works the professionals interested in the area feel very limited. The results reached from this inquiry demonstrate that the population has a superficial knowledge on the causes of the environmental problems, but they recognize their existence, have availability to participate of the mobilization that aim to guarantee security to the environment, they are aware which human activities like deforestation, forest fires and accumulation of garbage in the urban centers and others produce serious consequences to the environment and consequently her his lives, be through the global heating, natural catastrophes, desertification and appearance of diseases for consumption of foods contaminated by the form of unsuitable production and others. The politics and environmental management intends to limit the human actions that swallow damages to the environment, however it takes the realization of basic works as a principal objective, making the population aware as to the importance of the preservation of the natural resources, for which it start to point out the human being to him like an integrant being of the nature and which her each element have his importance, when there is so a relation of symbiosis between the men, animals, plants and the natural resources.